Large-scale label-free proteomics analysis of occupational poisoned patients of 1-bromopropane, workers exposed to 1-bromopropane and healthy individuals. (January 2018) - Miao, R; Ding, B; Zhang, Y; Zhao, R; Li, Y; Zhu, B
1-Bromopropane (1-BP) is an increasingly used chemical solvent for cleaning metals and gradually replacing spraying adhesives. Workers exposed to 1-BP (WBP) showed nervous system dysfunction and other symptoms. This study focused on the proteomic change between healthy individuals (HIs), WBP and poisoned patients with 1-BP (PBP). Total proteins from serum samples were isolated, and high-abundance proteins were filtered out. Large-scale label-free proteomics platform was utilized for protein identification and quantitative comparison, followed by biological function analysis by bioinformatics tools. Compared to HI, 99 proteins were up-regulated and 55 proteins were down-regulated in WBP; 59 proteins were up-regulated and 94 proteins were down-regulated in PBP. With WBP as control, 63 proteins were up-regulated and 127 proteins were down-regulated in PBP. These differently expressed proteins were mainly involved in the immune response, neuron system regulation, blood coagulation, wound healing, endopeptidase activity, lipid metabolic process and apoptosis. The proteomic profiling change of HI, WBP and PBP provides a comprehensive view on 1-BP poison through immune response, signal transduction, metabolism, coagulation and response to stress. This study expanded our understanding on early development and maintenance and provided more potential protein markers for diagnosis of 1-BP poisoning.